First Constraints on Helium +He3 Evolution in z = 3–4 Using the 8.67 GHz Hyperfine Transition - Cathryn M. Trott; Randall B. Wayth (The Astrophysical Journal, 2023)
We present the first constraints on the cross-correlation power spectrum of the He ii ( ^+ He ^3 ) signal strength using the redshifted 8.67 GHz hyperfine transition between z = 2.9 and 4.1 and with interferometric data obtained from the public archive of the Australia Telescope Compact Array (ATCA). 210 hr of observations of the primary calibrator source B1934-638 were extracted from data obtained with the telescope from 2014–2021, and coherently combined in a power spectrum pipeline to measure the He ii power across a range of spatial scales, and at three redshifts that span the period of helium reionization. Our best limit places the fluctuation of the brightness temperature to be less than 557 μ K on spatial scales of 30′ at z = 2.91, and less than 755 μ K on scales of 30′ at z = 4.14 (2 σ noise limited). We measure a temperature of 489 μ K at z = 2.91. ATCA’s few antennas and persistent remaining radio frequency interference in the data prevent deeper integrations improving the results. This work is a proof of principle to demonstrate how this type of experiment can be undertaken to reach the 0.01–1 μ K level expected for the helium signal at z ∼ 4.